Oral Risk Factors in Patients with Cancer Undergoing Chemotherapy - A Pilot Study - Anupama Aradya; P. K. Kiran; K. N. Raghavendra Swamy; Vidya G. Doddawad; Narahari Ranganatha; Koduru Sravani (Wolters Kluwer Medknow Publications, 2024)
Background Treatment modalities for cancer including surgery, radiotherapy and chemotherapy, have some complications even in the oral cavity. The literature describes oral lesions that may arise as a result of chemotherapy. However, information regarding oral symptoms in advanced cancer patients is poor. Objective To identify the oral manifestations like oral mucositis, dry mouth and loss of taste in patients undergoing chemotherapy treatment. Methods We evaluated 60 patients affected by malignancy undergoing chemotherapy treatment. The clinical and pathological data such as age, gender, diagnosis of malignancy and types of treatments with anticancer chemotherapeutic drug treatment, were obtained. Patients were routinely evaluated for the presence of oral mucositis based on the Common Terminology Criteria for Adverse Events (CTCAE) v5.0 scale for adverse effects and graded. Other findings like dry mouth and loss of taste were recorded. Results Of the 60 patients, 40 (66.6%) were male, and 20 (33.3%) females with a mean age of 53.7 years. Most patients about 63% and 83% were diagnosed with dry mouth and loss of taste, respectively and 71% of patients had mucositis. Chemotherapy drugs like Cyclophosphamide, carboplatin, nanoxel, paclitaxel, oxaliplatin, docetaxel and doxorubicin, were directly associated with oral mucositis. Conclusion Patients treated with chemotherapy for cancer most often suffer from a multitude of intense and debilitating oral dysfunctions. Oral lesions found in patients undergoing chemotherapy were mucositis, dry mouth and loss of taste. These adverse effects and an appropriate symptomatic therapy need to be discussed with the patients. Chemotherapy has a significant but transient effect on the oral symptoms.